Cryptocarya alba (Peumo): an endemic Chilean tree with phytochemicals with bioactive potential - Fuentes-Barros, Gonzalo; Castro-Saavedra, Sebastián; Montalva, Nicolás; Mellado, Marco; Diaz-Valdés, Antonia; Guerrero-Rodríguez, Claudia; Echeverría, Javier (Frontiers in Pharmacology, 2025)
BackgroundCryptocarya alba (Mol.) Looser [Lauraceae], known as peumo, is an endemic species of the central Chilean landscape. C. alba has an essential ecological role in the threatened sclerophyllous forest, with traditional uses of leaves, bark, and fruits, and the biotechnological and pharmacological potential of its phytochemicals.PurposeThe aim is to present the first comprehensive review of the current state of knowledge regarding traditional uses, ethnopharmacology, chemical composition, pharmacokinetic profile, and biological activities of C. alba.MethodologyLiterature data on the traditional uses, ethnopharmacology, chemistry, and bioactivity of C. alba were primarily obtained from digital databases, including Scopus®, ScienceDirect®, SciFinder®, PubMed®, SciELO, and Google Scholar®, as well as from the scientific journal publishers’ platforms associated with these databases.Results and discussionTraditional uses include its role as a food source for prehistoric populations and ethnomedicinal applications for liver diseases, rheumatism, and infections. The aerial parts are rich in polyphenols, including chlorogenic acid, epicatechin, procyanidins, quercitrin, rutin, and hyperoside, as well as essential oils derived from the leaves. While it contains various alkaloids, only reticuline is present in significant amounts, contributing to the species' highly variable chemical composition. Studies evaluating the biological and pharmacological properties of its extracts and constituents are limited to a few in vitro and in vivo studies; to date, no preliminary or clinical studies are available.ConclusionThe review highlights the entire existing ethnographic and cultural context of C. alba, revealing a significant gap in information about the species. Although there is a strong historical component, it supports the bioactivity of its main secondary metabolites, given its chemical and pharmacological profile. Given the limited nature of current biological and pharmacological evaluation studies, future research should focus on advancing preclinical and clinical trials, as well as toxicology studies, to ensure the safe and effective use of this approach.